1997
DOI: 10.1074/jbc.272.31.19115
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-I Rapidly Activates Multiple Signal Transduction Pathways in Cultured Rat Cardiac Myocytes

Abstract: In response to insulin-like growth factor-I (IGF-I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(107 citation statements)
references
References 77 publications
2
103
0
2
Order By: Relevance
“…Primary cultures of neonatal cardiac myocytes were prepared as described previously. 9 Cultures were enriched with cardiac myocytes by preplating for 60 minutes to eliminate fibroblasts. More than 90% of the cells were identified as cardiac myocytes by immunocytochemistry with anti-sarcomeric α-actin (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cultures of neonatal cardiac myocytes were prepared as described previously. 9 Cultures were enriched with cardiac myocytes by preplating for 60 minutes to eliminate fibroblasts. More than 90% of the cells were identified as cardiac myocytes by immunocytochemistry with anti-sarcomeric α-actin (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…9 Likewise, PI 3-kinase has a number of downstream targets, including the Akt protooncogene, 10 a serine/threonine protein kinase that is activated by the inositol lipid products of the PI 3-kinase reaction. 11 Activation of Akt has been shown to promote survival of some cell types, including neurons and lymphocytes.…”
mentioning
confidence: 99%
“…The intracellular signal pathway(s) involved in the transduction of IGF-I-induced cardiomyocyte hypertrophy was systematically investigated by Foncea and coworkers (11). The authors concluded that, in primary rat cultured cardiomyocytes, IGF-I activates multiple signal transduction pathways that involve IGF-IR b-1 subunit autophosphorylation, tyrosine phosphorylation of insulin receptor substrate (IRS)-1, phosphatidylinositol (PI) 3-kinase, phospholipase C (PLC)-g1, activation of the mitogen-activated protein kinase (MAPK)-extracellular signal-regulated kinase (ERK) cascade, and p90 S6 kinase (RSK), which were associated with an increased protein synthesis, as assessed by […”
Section: In Vitro Studiesmentioning
confidence: 99%
“…However, p90 RSK phosphorylation shows the total levels of the homologous phosphorylated sites of RSK1, RSK2, and RSK3. Assay for p90 RSK Activity-p90 RSK activity was measured by an immune complex kinase assay using an S6 peptide AKRRRLSSLRA as a substrate according to the procedure recommended in the S6 kinase assay kit (Upstate Biotechnology, Inc.) (38,39). Briefly, cell lysates were prepared from JB6 Cl 41 cells or JB6 Cl 41 cells with DNM-JNK1, DNM-p38, or DNM-ERK2 grown in 100-mm dishes.…”
mentioning
confidence: 99%